O processo de internacionalização entre os programas de pós-graduação de sociedade, cultura e fronteiras da Unioeste (Brasil) e educación con énfasis en gestión de la educación superior da UNE (Paraguai) - Abreu, Tânia Marta Moreira de (2024)
This research aims to carry out an investigation into the internationalization process between the Graduate Programs Master's and Doctorate in Society, Culture and Borders State University of West Paraná - UNIOESTE campus of Foz do Iguaçu, Brazil and Postgraduate Doctorate Program in Education with an emphasis on Management of Higher Education at the Universidad Nacional del Este – UNE campus Ciudad del Este, Paraguay, aims to problematize the engendering of the theme Internationalization in Stricto Sensu training, with a view to proposing the permanent feasibility of the internationalization process in both Universities. This research will be based on the analysis of the Institutional Internationalization Plans and the Pedagogical Political Projects of Postgraduate courses and, from this, elaborate proposals for Internationalization and integration actions that can be carried out effectively, among the border public Universities from Brazil and Paraguay, which will be observed from their Institutional documentation, through the legislation and educational guidelines in force in each country, with the aim of creating indicators that demonstrate the Internationalization Process, using the methodology of extraction and analysis of content by Laurence Bardin (2010). This is a research on integration and internationalization between Frontier Universities, of a qualitative nature, involving a triangulation of data, divided into a bibliographical research, a documental one and a field one, with a view to apprehending the current scenario of Internationalization in Graduate studies in Brazil and Paraguay, with the aim of contributing to national scientific development. It was found that internationalization was already taking place between the MS and PhD courses at PPGSCF. Also, some UNIOESTE professors were teaching online UNE classes, which led to the development of new subjects in partnership. These subjects help show that new educational technologies are the most efficient way for internationalization to take place, since they can help students from other countries to access courses, since their greatest difficulty is going to the university. In this regard, a technical, scientific, educational, and cultural cooperation agreement was approved throughout this research to increase internationalization, developing joint programs and projects. The sharing of knowledge, experience, and information took place during this research, which exceeded expectations as it helped elaborating the necessary documents for a co-tutorship to be carried out between UNIOESTE and UNE, though bilateral double graduations are still not a reality. It is noteworthy that this research went beyond its original goals, since its analysis of the current internationalization situation led to immediate practical results, such as to an update to an agreement between the universities which, as we found during our investigation, was expired. It also led to the elaboration of a minute for the cooperation between these universities, which supported the creation of internal legislation in the universities.